PROTECTING WORKERS' RIGHTS: A FAIR AND SUSTAINABLE LABOUR PROTECTION POLICY - Sulaiman; Fitriani Abdullah; Lhery Swara Oktaf Adhania (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The right to work, the right to fair wages, the right to associate and assemble, the right to security and health protection, the right to legal proceedings, the right to equal treatment, the right to personal secrets, and the right to freedom of conscience are just a few of the rights of workers that generally need to be upheld. Among the rights of entrepreneurs are the following: creating work rules and agreements; terminating employees; closing the business; forming and joining a corporate organization; and assigning a portion of the work to another business. In the area of employment, legal enforcement, guidance, and supervision can all be used to achieve the protection of workers' rights. According to justice, laborers have an equal and free status. In actuality, though, employers' and employees' positions are frequently uneven. There are still a number of troubling barriers present, such as: regulatory issues; cultural issues affecting employees, employers/entrepreneurs, and law enforcement; The employer and the employee are not equal in practice, despite their equality in theory; this includes the employer's ability to uphold workers' rights. This study does an exploratory review of the literature using a qualitative descriptive methodology. This research discusses labor protection theory, workers' rights and obligations, labor protection policies, shortcomings and obstacles in policy implementation.